Burden of serious fungal infections in Tanzania. (9th October 2015) - Faini, Diana; Maokola, Werner; Furrer, Hansjakob; Hatz, Christoph; Battegay, Manuel; Tanner, Marcel; Denning, David W.; Letang, Emilio
Summary: The incidence and prevalence of fungal infections in Tanzania remains unknown. We assessed the annual burden in the general population and among populations at risk. Data were extracted from 2012 reports of the Tanzanian AIDS program, WHO, reports, Tanzanian census, and from a comprehensive PubMed search. We used modelling and HIV data to estimate the burdens of Pneumocystis jirovecii pneumonia (PCP), cryptococcal meningitis (CM) and candidiasis. Asthma, chronic obstructive pulmonary disease and tuberculosis data were used to estimate the burden of allergic bronchopulmonary aspergillosis (ABPA) and chronic pulmonary aspergillosis (CPA). Burdens of candidaemia and Candida peritonitis were derived from critical care and/or cancer patients' data. In 2012, Tanzania's population was 43.6 million (mainland) with 1 500 000 people reported to be HIV‐infected. Estimated burden of fungal infections was: 4412 CM, 9600 PCP, 81 051 and 88 509 oral and oesophageal candidiasis cases respectively. There were 10 437 estimated posttuberculosis CPA cases, whereas candidaemia and Candida peritonitis cases were 2181 and 327 respectively. No reliable data exist on blastomycosis, mucormycosis or fungal keratitis. Over 3% of Tanzanians suffer from serious fungal infections annually, mostly related to HIV. Cryptococcosis and PCP are major causes of mycoses‐related deaths. National surveillance of fungal infections is urgently needed.